Technology's edge: The educational benefits of computer-aided instruction - Lisa Barrow; Lisa Markham; Cecilia Elena Rouse (Federal Reserve Bank of Chicago, 2007)
Because a significant portion of U.S. students lacks critical mathematic skills, schools across the country are investing heavily in computerized curriculums as a way to enhance education output, even though there is surprisingly little evidence that they actually improve student achievement. In this paper we present results from a randomized study in three urban school districts of a well-defined use of computers in schools: a popular instructional computer program which is designed to teach pre-algebra and algebra. We assess the impact of the program using statewide tests that cover a range of math skills and tests designed specifically to target pre-algebra and algebra skills. We find that students randomly assigned to computer-aided instruction score at least 0.17 of a standard deviation higher on a pre-algebra/algebra test than students randomly assigned to traditional instruction. We hypothesize that the effectiveness arises from increased individualized instruction as the effects appear larger for students in larger classes and those in classes in which students are frequently absent.
Keywords: 330; Schule; Lehrmaterial; Innovation; E-Learning; Bildungsertrag; USA; Schule; Lehrmaterial; Innovation; E-Learning; Bildungsertrag; USA